Pengaruh Transformational Leadership, Communication dan Work Environment terhadap Kinerja Perangkat Desa melalui Job Satisfaction Sebagai Variabel Mediasi - Dala Noor Iftikhar; Yasmin Mutiaramadhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Human resources play a fundamental role as a key component in supporting the success of an organization or agency, including village governments, as they serve as the link between formulated visions, missions, and targets and their actual implementation in the field. This study specifically focuses on examining the influence of transformational leadership, communication, and the work environment on the performance of village officials, with job satisfaction as a key mediating variable. The research method employed a quantitative approach with purposive sampling, involving 79 village officials deemed representative of the population. The findings indicate that transformational leadership partially has a significant impact on increasing the motivation, loyalty, and work ethic of village officials, as visionary leaders are able to direct, inspire, and encourage employees to work more optimally. Communication has also been shown to play a significant role, as open, two-way, and transparent communication minimizes misunderstandings and creates harmonious working relationships among employees and between superiors and subordinates. A conducive work environment, both physically, psychologically, and socially, contributes to a sense of security, comfort, and higher work morale. Furthermore, this study confirms that job satisfaction is a crucial mediating factor in linking transformational leadership, communication, and the work environment with the performance of village officials. This is because when employees are satisfied with their jobs, their commitment, productivity, and dedication to their tasks increase significantly. Therefore, this study emphasizes the need for an integrated strategy in human resource management at the village level, with an emphasis on an inspirational leadership style, an effective communication system, the creation of a healthy work environment, and increasing job satisfaction as a sustainable effort.